Baculovirus infection induces disruption of the nuclear lamina - Xiaomei Zhang (Nature Portfolio, 2017)
Abstract Baculovirus nucleocapsids egress from the nucleus primarily via budding at the nuclear membrane. The nuclear lamina underlying the nuclear membrane represents a substantial barrier to nuclear egress. Whether the nuclear lamina undergoes disruption during baculovirus infection remains unknown. In this report, we generated a clonal cell line, Sf9-L, that stably expresses GFP-tagged Drosophila lamin B. GFP autofluorescence colocalized with immunofluorescent anti-lamin B at the nuclear rim of Sf9-L cells, indicating GFP-lamin B was incorporated into the nuclear lamina. Meanwhile, virus was able to replicate normally in Sf9-L cells. Next, we investigated alterations to the nuclear lamina during baculovirus infection in Sf9-L cells. A portion of GFP-lamin B localized diffusely at the nuclear rim, and some GFP-lamin B was redistributed within the nucleus during the late phase of infection, suggesting the nuclear lamina was partially disrupted. Immunoelectron microscopy revealed associations between GFP-lamin B and the edges of the electron-dense stromal mattes of the virogenic stroma, intranuclear microvesicles, and ODV envelopes and nucleocapsids within the nucleus, indicating the release of some GFP-lamin B from the nuclear lamina. Additionally, GFP-lamin B phosphorylation increased upon infection. Based on these data, baculovirus infection induced lamin B phosphorylation and disruption of the nuclear lamina.